The Problem of Modeling the Practice of Heat Treatment in the Preparation of Shafts of Technological Machines (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this article, the solution of the problem posed by the method of modeling the process of thermal processing is considered in solving the problems of managing and facilitating the technological process of manufacturing the shafts of technological machines and various techniques. As a result of theoretical studies, it was stated that the proposed thermal treatment model of shafts allows for rational control of the direction and amount of internal stresses in the preparation of shafts of technological machines and other techniques.